Profeciency in Patient Interaction an essential tool for the Health Provider: A Review of Literature - Mukherjee, Sananda; Lakshmikantha, Nandini (International Journal of Psychosocial Rehabilitation, 2020)
The communication that takes place inside a hospital not only involves the doctor and patient, but widely includes many others connected in the service system. As a patient enters the hospital for treatment, a rapport is established between him/her and the clinical support staff of the hospital. From the time of entry to his/her exit time during the process of treatment will have a smooth transit if the service seeker feels happy and contented with the attention he/she has received. However in recent times, cases of discomfort and misconception during the treatment have been reported widely in various media formats and serious concern arises when such situations turn violent. Researchers across the globe have conducted studies in this area and have tried to examine and analyse the situation. The opinion of various reserchers with reference to inter personal communication has been compiled and analysed in this paper.